Dinamika Kompetensi Pengasuhan Islami - Ahmad Naqieb Alinaksi; Endah Puspita Sari (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2015)
The purpose of this study are to know about what are the competencies in Islamic Parenting and its dynamics There are two subjects in this study, the parents who have an Islamic background and rated by general public as experts in Islamic religion. This study using qualitative research design. The data used in this study were taken by in depth interview method. Interviews were conducted with the subjects and research informants. The results of Islamic parenting competence from the first subject are tarbiyah, akhlakul karimah, exemplary, and communication. While on the second subject, there is only one competence of Islamic parenting, tarbiyah. The good preparation before marriage is very importance for parents, even start from the process to find partner. It makes parent ready and can provide all the parenting competencies. In addition, the competencies will be run well if there is cooperation between father and mother in parenting. Keywords: dynamics, competence. Islamic Parenting